2002
DOI: 10.2136/vzj2002.0172
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hydraulic Nonequilibrium on Pressure Plate Data

Abstract: ards, 1948, 1965 Richards and Ogata, 1961), has been the method of choice for determining water-retention Pressure plates are used routinely to measure water-retention charcharacteristics for literally thousands of soil samples acteristics of soils. Plates of varying porosity are used, depending on the pressure range of interest. For applied pressures up to 1.5 MPa, during the past 50 yr (Clapp and Hornberger, 1978; 15-bar porous ceramic plates with fine porosity are used because of Rawls et al., 1982). Spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 0 publications
1
22
0
2
Order By: Relevance
“…Several samples are allocated on the plate and if they are very heterogeneous, there is a possibility that not all will reach equilibrium at the same time, when the samples are removed from the chamber. The comparison of results using WP4 and the Richards chamber with disturbed samples is useful because it eliminates the porosity configuration effect, since the higher water content observed in the Richards chamber could have occurred in function of the soil water extraction having been incomplete, not reaching equilibrium (Gee et al, 2002;. Klein et al, 2006), due to the conductivity of the water being very low at this potential (Angelotti Netto & Fernandes, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Several samples are allocated on the plate and if they are very heterogeneous, there is a possibility that not all will reach equilibrium at the same time, when the samples are removed from the chamber. The comparison of results using WP4 and the Richards chamber with disturbed samples is useful because it eliminates the porosity configuration effect, since the higher water content observed in the Richards chamber could have occurred in function of the soil water extraction having been incomplete, not reaching equilibrium (Gee et al, 2002;. Klein et al, 2006), due to the conductivity of the water being very low at this potential (Angelotti Netto & Fernandes, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Since equilibrium time grows with the square of the length of the sample (Miller, 1980), equilibration times of large samples become prohibitively long for high suctions. Nonequilibration is in particular a problem for sands, where higher tensions can only be reached by equilibration via the gas phase (Gee et al, 2002). For the dry range of a retention curve, there are not many alternatives.…”
Section: Hydrostatic Equilibrium Methodsmentioning
confidence: 99%
“…Repeated measurements at increasing pressures are performed to obtain several measurements of water content as function of the applied pressure (water potential). Several authors [38][39][40] showed that measurements with pressure plates are in error at potentials below −100 to −500 J kg −1 .…”
Section: Pressure Plates Apparatusmentioning
confidence: 99%